A Mobile Application As a Tool for Sustainable Development in Protected Areas (a proposal for the case of Arrabida Natural Park) - Khodzhaeva, Valeriia (2021)
Protected natural areas are designed to preserve biological and landscape diversity and ensure sustainable environmental development. Huge territories face great challenges in the management of sustainable tourism, which are very difficult to control due to uncontrolled traffic capacity and the lack of awareness of visitors about the uniqueness of the park. The best way to convey information to the masses is information technology, which almost every modern person has. The goal of this project is to develop and promote a mobile application to help developing sustainable tourism in protected areas using the case of Arrabida Natural Park.